2011
DOI: 10.1308/003588410x12771863936927
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve and voice preservation: routine identification and appropriate assessment – two important steps in thyroid surgery

Abstract: Despite identification and preservation of RLN, patients can develop postoperative voice change and RLNP although all voice change cannot be attributed to damaged RLN. Proper assessment of vocal cord functions by I/L and D/L laryngoscopy is required to rule out injuries to these nerves. Risk of damage is higher in patients undergoing more difficult surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…Bifurcation of the RLN is known to be an important risk factor for postoperative vocal cord paresis. Longer distance of the bifurcation from the NEP has been implicated as a determinant of nerve injury during thyroid surgery . The difference in distance of RLN bifurcation from the NEP between Caucasian patients and African Americans patients does not reach statistical significance in our study ( P = 0.30; Table ).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Bifurcation of the RLN is known to be an important risk factor for postoperative vocal cord paresis. Longer distance of the bifurcation from the NEP has been implicated as a determinant of nerve injury during thyroid surgery . The difference in distance of RLN bifurcation from the NEP between Caucasian patients and African Americans patients does not reach statistical significance in our study ( P = 0.30; Table ).…”
Section: Discussioncontrasting
confidence: 75%
“…Extralaryngeal RLN bifurcation typically occurs within 20 mm of its entry point into the NEP and represents an area of great vulnerability to damage during thyroid surgery (Fig. ) . Here the branched nerve, of a more diminished caliber, is vulnerable to damage by complete transection, compression, and traction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Review of literature revealed that the prevalence of RLN palsy varies from centre to centre depending upon the level of experience in thyroid surgery and the nature of surgery. Aytec and colleagues 15 reported 3.5% and 1.2% incidence of transient and permanent RLN injury, respectively and Hayward et al, 7 reported that permanent RLNP occurs in 0.3-3% of cases, with transient palsies in 5-8%, Chaing 14 has reported figures of 5.1% and 0.9% for transient and permanent RLN injury.…”
Section: Results and Observationsmentioning
confidence: 99%
“…4 Therefore, methods that can reduce the incidence of this complication are of great interest. 5 The most important aspect of effective and safe surgical approach is an adequate knowledge of surgical anatomy and pathophysiology in combination with meticulous handling and dissection of tissue in the correct surgical plane. RLN is located anterior to the tracheoesophageal sulcus (41.6%), posterior to the inferior thyroid artery (35.8%), lateral to Berry's ligament (88.1%), below the inferior rim of the inferior constrictor muscle (90.4%), and entering the larynx before its terminal division (54.6%).…”
Section: Introductionmentioning
confidence: 99%